ENVIRONMENTAL SUSTAINABILITY ANALYSIS IN KAMAJAYA HOUSING IN SUPPORTING THE FEASIBILITY OF LIVING - Mei Fajri Anugrah Sukma; Heru Setiyo Cahyono; Annisa' Carina (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
The increasing need for housing as the population grows is a challenge for sustainable environmental management. Housing is an important element of urban ecosystems that affect quality of life. Kamajaya housing in Singosari District is designed for the needs of modern housing with environmental aspects, but there is still a need for deeper analysis regarding the application of sustainability principles. Environmental sustainability in housing includes energy use, water and waste management, green space, and climate change adaptation. Sustainable housing improves air quality, resident health, and comfort. This study aims to evaluate the sustainability of Kamajaya Housing to provide recommendations for improving environmental quality and supporting sustainable housing policies. Suitability of Space Utilization Activities (KKPR) is a tool in spatial planning to ensure optimal and sustainable land use by considering environmental, social, and economic aspects. The Ministry of Fisheries and Fisheries prevents land conflicts, preserves the environment, and encourages sustainable economic growth. The implementation of the KKPR requires adequate data, conflict of interest management, and strong analytical capacity. The results of the study show that the Building Boundary Line (GSB) is decided to have a minimum distance of GSB of 5 m + 5.5 m. The distance of 11 m for this measurement is in accordance with the IKKPR Decree, namely the minimum distance of GSB 5 m + 5.5 m measured from the outermost side of a building mass to the Road Axle which is the measurement reference. Kamajaya Housing occupies 58.02% of the Land Area so that the KDB is less than 70% of the Land Area. KDH Residential Buildings less than 10 % Land area with RTH Composition: Garden: 132 m2. Net Needs for Residential Buildings, then the amount of water needs has been able to be met by the Clean Water Source by the PDAM network, which is 125 Liters / Minute. Referring to SNI 03 – 7065 : 2005 Plumbing System Planning Procedures. Consumption of Residential Houses with Occupants amounting to 4 people with effective activities per day is 8 hours, the waste of dirty water is 65 liters. Referring to SNI 03 – 7065 : 2005 Plumbing System Planning Procedures. For rainfall figures are = 8 Liters / Minute